Current Condition of Private Security Industry in Mongolia - Lkhagvamaa, Galbat; Lee, Julak (Advances in Social Sciences Research Journal, 2016)
Since 1990, with its transition to the market economy relations and with its newly built economic sector based on private ownerships, the private security sector has been developed in keeping with international best practices and standards in terms of its legal basis, structure and organization and, equipment and technology. The main objective of this study was to analyse current condition of private security in Mongolia and findings show that, in general, the security service in Mongolia is being developed with the two types of security service including the proprietary service and the contract service. The findings of the research give quite a complex picture of the development of private security in terms of current condition of private security in Mongolia. Therefore, the findings can be used to influence certain roles within the private security sector, but also to aid the development of the new strategic document on the further expansion of the private security industry in Mongolia which state policy-makers will prepare.